2017
DOI: 10.1016/j.jbi.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Identifying complexity in infectious diseases inpatient settings: An observation study

Abstract: Background Understanding complexity in healthcare has the potential to reduce decision and treatment uncertainty. Therefore, identifying both patient and task complexity may offer better task allocation and design recommendation for next generation health information technology system design. Objective To identify the specific complexity-contributing factors in the infectious disease domain and the relationship with the complexity perceived by clinicians. Method We observed and audio recorded the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…A total of 2 investigators will independently code the transcripts from the team CTA interviews and merge the individual codes into subthemes and later into broader themes through a process of negotiated consensus. We will code based on a qualitative content analysis process [61-63]. We will use ATLAS.ti software for data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 2 investigators will independently code the transcripts from the team CTA interviews and merge the individual codes into subthemes and later into broader themes through a process of negotiated consensus. We will code based on a qualitative content analysis process [61-63]. We will use ATLAS.ti software for data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As PGx becomes more widely accessible, it is important that patients share results with family members in order to effectively identify individuals that are at risk for adverse drug events or medication failures. Also, with the increasing complexity of patients' data from discrete sources, it is imperative to integrate family PGx data to optimize therapy outcomes for family members [30][31][32][33].…”
Section: Pharmacogenomic Cascade Testing (Phact)mentioning
confidence: 99%
“…We showed that the introduction of technological communication channels didn’t substantially improve the engagement of these patients and for some of the patients it even reduced communication with health care professionals. Based on these findings, we think that improving patient engagement cannot rely solely on technological solutions; rather, these solutions must be accompanied by complementary means [ 65 ].…”
Section: Discussionmentioning
confidence: 99%